Idiosyncratic Ag7Pt2O7: An Electron Imprecise yet Diamagnetic Small Band Gap Oxide - Thakur, Gohil S.; Dinnebier, Robert; Hansen, Thomas C.; Assenmacher, Wilfried; Felser, Claudia; Jansen, Martin (Angewandte Chemie International Edition, 2020)
The seminal qualitative concepts of chemical bonding, as presented by Walter Kossel and Gilbert Newton Lewis back in 1916, have lasting general validity. These basic rules of chemical valence still serve as a touchstone for validating the plausibility of composition and constitution of a given chemical compound. We report on Ag7Pt2O7, with a composition that violates the basic rules of chemical valence and an exotic crystal structure. The first coordination sphere of platinum is characteristic of tetravalent platinum. Thus, the electron count corresponds to Ag7Pt2O7*e−, where excess electrons are associated with the silver substructure. Such conditions given, it is commonly assumed that the excess electrons are either itinerant or localized in Ag−Ag bonds. However, the material does not show metallic conductivity, nor does the structure feature Ag-Ag pairs. Instead, the excess electrons organize themselves in 2e−4c bonds within the silver substructure. This subvalent silver oxide reveals a new general facet pertinent to silver chemistry.
CRIS-Team Scopus Importer:2022-04-14
Keywords: electron diffraction; silver clusters; silver oxoplatinate; subvalent silver